EFFICIENCY OF BANKS IN DEVELOPING COUNTRIES: A CASE STUDY OF INDIA. - Suchak, Riddhi (2013)
An unbalanced panel dataset of 282 banks over 10 years, which included the commercial banks, the co-operative banks and other financial institutes, was put to test for efficiency. The intermediation approach is applied to find the variables for this study. The variables include three inputs and three outputs. Distribution Free Approach (DFA) and Stochastic Frontier Approach (SFA) are two efficiency approaches implemented to find the efficiency. Under these approaches two functions were utilized, cost and production function. Production function further helped in finding the technical efficiency, which included market variables. The results showed satisfactory production and technical efficiency in the stochastic approach. The technical efficiency is better than the production efficiency, which shows a good repose of the banks towards the market variables. A slight dip can be seen in the technical efficiency in the year 2008, which is presumed to be due to the recession that hit the world. However, the cost efficiency exhibited poor results, which showed inefficiency on behalf of the management to administer the price of input to get maximum output. In my opinion if the Indian banks want to become highly efficient and compete with the foreign banks in Indian market, they need to improve the cost structure by either reducing the costs like labor or non-operating expenses or increase the output quantity to increase the profits.